Reality and Experience - Kaila, E. author. aut Link
XLV, 328 p.
Keywords: Philosophically, there is a book which was a tremendous experience for me: Eino Kaila's hychology of the Person ality _ His thesis that man lives strictly according to his needs - negative and positive - was shattering to me, but terribly true. And I built on this ground. Ingmar Bergman J 1. This introductory essay is neither intended to be a full presentation nor to be a critical evaluation of the contributions to philosophy made by Eino Kaila. Kaila's work will speak to the reader through the four papers here published in English translation from the German. They belong in the tra dition of the Vienna Circle and of logical empiricism. They cover, however, only one period or sector of Kaila's rich and varied life-work. This is the sector best integrated into the mainstream of contemporary philosophic thinking. The primary aim of this essay is to portray an impressive intellectual personality and to make a modest contribution to Finnish and Scandinavian intellectual history. Much of its content may be thought to be of 'local' relevance only. But considering the position which Kaila held in his country and considering his decisive influence on the development of philosophy in Finland, I hope that this local background will also interest an international circle of readers.